Etimologijos pastabos V. Nomina postverbalia indas, pergas, išeiga ir kt. - Smoczyński, Wojciech (Baltistica, 1998)
ETYMOLOGICAL REMARKS. PART V: Postverbal derivatives of the type indas, pergas, išeigaCertain two-syllable Lithuanian nouns at first glance seem to be primary formations, but in fact they are not. Cf. pãdas like vãdas, pradžià like vadžià,, pardà like vadà, ãpstas like mãstas, próga like úoga, etc. What separates these quasiprimary words is the presence of the prefixes pa-, pra-, par-, ap-, pro-. Pursuant to this observation it has been proposed to etymologize the Lithuanian words with the help of a model suggested by Vedic composita with a final zero-grade root member, e.g. duḥ-sth-a-, su-ṣṭh-u-etc. Applied to the Lithuanian material, this hypothesis yields the following analyses: pa-d-as, pra-d-jā with -d- from */dhh1V-/ related to */dheh1/ „put“; par-d-a, with -d- from */dh3-V-/ to */deh3-/ „give“, ap-st-as, with -st- from */sth2-V-/ to */steh2-/ „stand“; pro-g-a, with -g- from */gwh2-V-/ to */gweh2-/ „go”. The problem, however, is: (1) the Vedic material offers no parallel for adding preverbs to the zero grade of a verbal root to form a nomen compositum, (2) the compounds quoted from Vedic with su- and dus- are rather rare in other ancient languages, and in Balto-Slavic are not attested at all (apart from the hypothetical instances mentioned here). Hence we should look at the quasiprimary Lithuanian words from another angle. The author’s suggestion is that they are postverbal derivatives formed by replacing the verbal suffixes -ė(ti), -uo(ti) or -o(ti) by the nominal suffixes -a-, -ā-, -jā-, -ė-. Cf. pad-as
Keywords: lietuvių kalba; etimologija